Mechanisms of gut epithelial barrier impairment caused by food emulsifiers polysorbate 20 and polysorbate 80 - (:unkn) unknown (My University, 2023)
Background: The rising prevalence of many chronic diseases related to gut barrier dysfunction coincides with the increased global usage of dietary emulsifiers in recent decades. We therefore investigated the effect of the frequently used food emulsifiers on cytotoxicity, barrier function, transcriptome alterations, and protein expression in gastrointestinal epithelial cells. Methods: Human intestinal organoids originating from induced pluripotent stem cells, colon organoid organ-on-a-chip, and liquid–liquid interface cells were cultured in the presence of two common emulsifiers: polysorbate 20 (P20) and polysorbate 80 (P80). The cytotoxicity, transepithelial electrical resistance (TEER), and paracellular-flux were measured. Immunofluorescence staining of epithelial tight-junctions (TJ), RNA-seq transcriptome, and targeted proteomics were performed. Results: Cells showed lysis in response to P20 and P80 exposure starting at a 0.1% (v/v) concentration across all models. Epithelial barrier disruption correlated with decreased TEER, increased paracellular-flux and irregular TJ immunostaining. RNA-seq and targeted proteomics analyses demonstrated upregulation of cell development, signaling, proliferation, apoptosis, inflammatory response, and response to stress at 0.05%, a concentration lower than direct cell toxicity. A proinflammatory response was characterized by the secretion of several cytokines and chemokines, interaction with their receptors, and PI3K-Akt and MAPK signaling pathways. CXCL5, CXCL10, and VEGFA were upregulated in response to P20 and CXCL1, CXCL8 (IL-8), CXCL10, LIF in response to P80. Conclusions: The present study provides direct evidence on the detrimental effects of food emulsifiers P20 and P80 on intestinal epithelial integrity. The underlying mechanism of epithelial barrier disruption was cell death at concentrations between 1% and 0.1%. Even at concentrations lower than 0.1%, these polysorbates induced a proinflammatory response suggesting a detrimental effect on gastrointestinal health.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology; epithelial barrier; food emulsifiers; polysorbate-20; polysorbate-80; RNA-seq; targeted proteomics